REDOX AND THERMODYNAMIC INVESTIGATION OF 2-HYDROXYETHYLETHYLENEDIAMINETRIACETATOIRON(III) REACTION WITH 2-MERCAPTOETHANOLIC ACID IN A BICARBONATE-BUFFERED ENVIRONMENT - Onu, Ameh David; Nkole, Ikechukwu Ugbaga; Idris, Sulaiman Ola (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2025)
The coordination chemistry of hexadentate ligands is compelling, as it provides both kinetic and thermodynamic stability to the coordinated complex, facilitating electron distribution while preserving structural integrity. In this study, the redox behavior of the reaction between 2-hydroxyethylethylenediaminetriacetatoiron(III) (HEI) and 2-mercaptoethanolic acid (MEA) was investigated spectrophotometrically in a bicarbonate-buffered environment. The reaction followed first-order kinetics with respect to [HEI] and [MEA], with a 2:2 molar ratio observed. The reaction rate was significantly affected by increases in the ionic strength and the dielectric constant of the medium. Ion catalysis was evident, and variations in pH had a significant effect on the redox pathway. Activation enthalpy and Gibbs free energy, as determined via the Eyring–Polanyi equation, indicate that the reaction required additional thermal energy to proceed. The formation of thiyl radicals facilitated the conversion of the mercapto compound to a disulfide. A Michaelis-Menten-type plot (MMTP) supported the absence of intermediate species participation, as indicated by a negative result, further corroborated by matching spectroscopic spectra of reacted and unreacted mixtures. The proposed mechanism offers insight into the potential anticancer activity of mercaptoethanolic acid.